Clinico-pathological study of locally advanced breast cancer and their hormone receptor analysis - Jain, Sanjay; M., Guka Priyan K.; Songara, M. C. (International Surgery Journal, 2020)
Background: Breast carcinoma is one of the most common malignant tumor of women. Determination of estrogen receptors (ER) and progesterone receptors (PR) status, prior to therapeutic intervention has become standard practice. Survival and response to hormone therapy are most favorable among women who are receptor positive. The aim of this study is to assess the hormone receptor status in locally advanced breast carcinomas and correlate this reactivity pattern with tumor stage, clinical stage and lymph node metastasis. Objective of the study was to co-relate the locally advanced breast cancer and their hormone receptor analysis. Methods: Patients who visited Department of General Surgery, Hamidia Hospital, Bhopal were assessed clinically, radiologically and histopathologically and then ER and PR study was done, for a total of 50 cases were done. Results: In our study majority of the cases were locally advanced breast cancer (50%) which may be due to the low socio economic status, late presentation, pain tolerance, illiteracy and availability of the resources. Majority of cases were in postmenopausal, clinical stage 3 and histological grade 2. ER positivity 50% and PR positivity 44% and it was found that hormone receptor positivity was high in locally advanced breast cancers 63.5%. Conclusions: Hormone receptor analysis should be an integral part of initial workup of carcinoma breast, as the percentage of hormone receptor positivity is increasing in our population in locally advanced breast cancer. So locally advanced breast cancer can be diagnosed at an early stage by screening and conducting breast awareness programs.